Feasibility and acceptability pilot study of an online weight loss program in rural, underserved communities - Oliveira, Ashleigh; Alfouzan, Nouf; Yu, Jin; Yahya, Asma; Lammy, Kayla; Wright, Mary Liz; Reinhold, Diane; Peterson, Lisa; Brewer, Ashley; Liechty, Janet; Nakamura, Manabu T. (PeerJ, 2024)
Background The purpose of this intervention was to investigate the feasibility, acceptability, and preliminary effectiveness of an online weight loss program, EMPOWER, in rural, underserved communities. Methods Adults with a body mass index (BMI) ≥ 25 kg/m2 living in rural counties were recruited through collaboration with University of Illinois Extension. The intervention lasted 1 year including online educations sessions, nutrition and lifestyle coaching, and diet and weight monitoring via a novel web application, MealPlot. Feasibility was measured by enrollment attainment, participant retention, online education session completion, and completion of anthropometric and dietary measures. Acceptability was measured by survey using Likert scales of satisfaction for all program components. Anthropometric measurements, 24-h dietary records, and food frequency questionnaires (FFQs) were measures of program efficacy. Additionally, two interviews were collected for program feedback. Results Enrollment of 16 participants was attained, however due to higher than anticipated dropout (retention 62.5%, N = 10) at 3-months, 62.5% of the education sessions were completed and 75.0% of anthropometric and dietary measures. The average satisfaction rating for the comprehensive program was 4.2/5 with lowest satisfaction being the MealPlot web application 2.7/5 (N = 11). On average a clinically significant (≥5% baseline weight) weight loss of 6.2 ± 6.0% body weight or 5.7 ± 5.3 kg and improvements to protein and fiber intake at 12 months (N = 10) were observed. Conclusions A novel online weight loss program showed adequate to strong feasibility and acceptability and preliminary results indicating efficacy among a pilot sample of rural residents. Future studies are required to investigate means of improving retention and reducing the burden on program collaborators.
Keywords: Rural; Weight; Obesity; Protein; Fiber; Weight loss; Rural health; Diet; Nutrition; Nutritional geometry